Microwave sensors for the non-invasive monitoring of industrial and medical applications. Issue 2 (11th March 2014) - Korostynska, O.; Mason, A.; Al-Shamma'a, A.
Abstract : Purpose: – This paper aims to discuss the general principles behind the microwave sensing and demonstrates the potential of cavity microwave resonator device in real-time monitoring for: environmental monitoring with the focus on wastewater pollution, a system for oil/gas/water content evaluation in a dynamic pipeline, a system for real-time determination of bacteria concentration and a method for non-invasive glucose determination. Design/methodology/approach: – Microwave sensing is a rapidly developing technology which has been successfully used for various industrial applications including water level measurements, material moisture content, in construction industry for non-invasive evaluation of structures and even in the healthcare industry for non-invasive real-time monitoring of glucose in diabetic patients. Novel microwave cavities designed and tested for specific applications are presented. Findings: – The paper provides experimental results of testing the novel microwave sensing systems in a range of industrial and healthcare applications and discusses the potential of these systems for real-time monitoring of processes and parameters. Research limitations/implications: – The concept of real-time microwave sensing was successfully tested, but further experiments are required to account for possible interference mechanisms before it can be used commercially on a large-scale. Practical implications: – It is suggested that a novel approach to wastewater monitoring, namely using specially designed microwave cavity sensors, could lead to a successful development of an advanced platform capable of providing for a real-time detection of water content with superior sensitivity. Also, a system for real-time multiphase fluid composition monitoring is reported, which is essential for sustainable oil industry operation. Originality/value: – The paper illustrated the potential of microwave sensing as a real-time monitoring platform for a broad spectrum of commercial applications, with a focus on system developed by the authors, namely, for the monitoring of a multiphase fluid flow in a dynamic oil pipeline, for real-time monitoring of nutrients concentration in wastewater and for healthcare industry, in particular for real-time non-invasive determination of the glucose levels and bacteria concentration.